Transnacionálne sietě a diskurzy v participatívnej ochrane morských korytnačiek na Komorách - Marek Mikuš (AntropoWebzin, 2009)
This work examines how participatory conservation projects of the NGO Community Centred Conservation (C–3) in the Comoros draw on global environmental ”narratives” and constitute transnational social fields and ”actor-networks”. In sustainable development and natural resource conservation, ”community-based” approaches, requiring participation of people living in and around protected areas and linking conservation objectives with local development needs, now take the centre stage. Policy shifts are critically conceptualised as a  procession of narratives – discursive formations which facilitate explaining environmental change, decision-making and the replication of adopted modes of action across space and time. Narratives can only be superseded by similarly parsimonious and convincing ”counter-narratives” of which participatory conservation is an example. Implementation of such globalised and globalising policies is showed by an actor-oriented anthropology of development to be a socially constructed and negotiated process rather than straightforward execution of a plan of action with expected outcomes. The paper looks at the interactions between official representations and everyday ”strategies” of various participants, including local and expatriate actors. It evades the assumption that mobile conservation and development practitioners and local people and ”development agents” inhabit clearly separated instituti-onal and knowledge worlds. Ethnographic interpretation of C–3’s activities in Mohe´li inspired by the Actor Network Theory has identified some strategies and ”translations” between actors involved in these actor-network constructions. While C–3 attempts to control these constructions varying from conflict to co-operation, power relationships in these transnational actor-networks remain fairly open-ended.